Validating School Counselor Professional Identity: Response to “Suicide Intervention in Schools” - Donna Gibson (Teaching and Supervision in Counseling, 2022)
In response to the manuscript of “Suicide intervention in schools: If not school counselors, then who?” the roles and responsibilities of school counselors and educators are highlighted as to effective preparation for suicide intervention. Although preparation in training is needed due to the increasing rates of suicide in K-12 student populations, the professional identity development of school counselors is examined as it applies to the growing mental health needs in schools. Implications for counselor educators and school counselors in their responsibility for training and prioritizing needs to address are provided.
Keywords: school counselor professional identity